Rural Landscape Change: Sketches of Transformation in E. Columbia County, Wisconsin - Stum, Brian; Krawczyk, Phoebe; Duffy, Kaylie; Banetzke, Randy (My University, 2013)
The rural landscape of America?s heartland encountered tremendous change over the past century. The effects of industrialization and a rapidly shifting economy during the late 19th century, forced family farmers to contend with an entirely new set of processes. These processes continue into the 21st century, and the increased demand for alternative energy, conservation, and food security, calls for a focus on rural land use. Our paper seeks to examine the structural, socio-economic, and ecological changes in Eastern Columbia County, Wisconsin by 1) distributing surveys to residents of Eastern Columbia County to examine the effects of the Glacier Hills Wind Park, 2) by interviewing the owners of the Fountain Prairie Inn and Farms, and 3) by collecting observational ecological data from the disused Banetzke Farm to evaluate ecological land use change over time. Our survey results revealed that local attitudes toward recent landscape change correlate more with proximity to the site of landscape change than with length of residency. In addition, our interview with the owners of Fountain Prairie Inn and Farms illustrated that many of today?s small farms must operate pro-actively, adopting environmentally friendly and financially viable methods to succeed. Conversely, on the Banetzke farm we observed an ecological transformation from cropland to forest due to financial difficulties and farm accidents. We concluded that rural landscape change happens on many different scales and for a variety of reasons. While a common cause may still bring communities together, the interplay between development, employment and personal advancement supersedes collective experience.
Includes Maps, Air photos, Tables, Photographs, Appendices and Bibliography.
Keywords: Landscape change; Rural; Columbia County